ACT-16 THE POTENTIAL OF HYPOFRACTIONATED RADIOTHERAPY AND BEVACIZUMAB FOR GLIOBLASTOMA TREATMENT. (16th December 2019) - Hata, Nobuhiro; Mizoguchi, Masahiro; Kuga, Daisuke; Hatae, Ryusuke; Sangatsuda, Yuhei; Akagi, Yojiro; Amemiya, Takeo; Fujioka, Yutaka; Takigawa, Kosuke; Yoshitake, Tadamasa; Yoshimoto, Koji; Iihara, Koji
Abstract: INTRODUCTION: First-line bevacizumab (BEV) is now available as a treatment option for glioblastoma (GBM) patients with severe clinical conditions in Japan. However, the survival benefits remain controversial. As we have emphasized the combined effect of BEV and radiation therapy, the strategies; 1) first-line add-on BEV to TMZ-radiation for unresectable GBMs and 2) re-irradiation using IMRT under BEV administration for recurrent GBMs, have been positively applied. To elucidate these potential survival benefits, we retrospectively analyzed survival in GBM patients. METHODS: We analyzed survival in 101 patients with IDH-wild type GBM treated from 2006 to 2018. PFS and OS were assessed in two subgroups (TMZ and TMZ-BEV eras), and the correlations of prognostic factors with survival were evaluated. RESULTS: After BEV approval, OS prolongation tendency (median OS: 14.9 vs. 22.1 months; P = 0.52) was observed, and this tendency was clearer in unresectable cases (10.1 vs 16.1 m P = 0.38). Subanalysis showed a significant prolongation of prognosis in the MGMT unmethylated group (12.2 vs 16.7 m; P = 0.04). In 10 patients of recurrent GBMs receiving BEV combined re-irradiation, adverse events of Grade 3 or higher did not occur. All patients showed PR (N=5) or CR (N=5) after treatment. The mPFS and mOS from the recurrence were 4.3 and 9.4 months, however, no local relapse was observed at their second recurrences. CONCLUSIONS: Our treatment strategy has improved the outcome of high-risk cases after BEV approval. These results implied that hypofractionated radiotherapy under BEV administration might be an efficient treatment protocol as a first-line for high-risk cases, such as after partial excision and MGMT unmethylation.